PENGEMBANGAN MODUL MATEMATIKA MATERI RELASI DAN FUNGSI BERBASIS PEMBELAJARAN VISUAL, AUDITORIAL, DAN KINESTETIK (VAK) KELAS VIII MTs ASH-SHALIHIN GOWA - Magfiraturrahmah, Magfiraturrahmah; Sulasteri, Sri; Rahman, Ulfiani (Faculty of Tarbiyah and Teacher Training, 2025)
The lack of varied teaching materials and the inability to adapt to students' learning styles, as well as teacher-centered learning, encourage the development of learning innovations. Therefore, this study aims to develop a mathematics module based on Visual, Auditory, and Kinesthetic (VAK) learning. The research model used is ADDIE which consists of several phases, namely Analysis, Design, Development, Implementation, and Evaluation. The product developed is a teaching material, namely a VAK-based learning module on the material of relations and functions which was tested on 30 eighth-grade students at one of the MTs in Gowa. The instruments used in this study were expert validation sheets, student activity observation sheets, teacher activity observation sheets in the implementation of learning, student response questionnaires, teacher response questionnaires, and learning outcome tests. Based on the results of the trials conducted, this module meets the validity criteria with all instruments in the very high category. The practicality criteria are met with educator responses and learning implementation in the very good category. The effectiveness criteria are seen from student activities in the very good category), student responses in the very positive category, and learning completion reaching classical completion of 84%. Therefore, it can be concluded that the VAK-based mathematics module on the subject of relations and functions for grade VIII has met the criteria of validity, practicality, and effectiveness.